Petits riens sophocléens : Œdipe à Colone I - Liberman, Gauthier (Hyperboreus, 2020)
This two-part paper, one of a forthcoming series of “Sophoclea” or “*Sophocleuncula”, deals with not a few diﬃcult passages of this poet’s last tragedy Oedipus at Colonos and is meant by its author to contribute to rethinking the numerous exegetical and critical issues which the text of this unduly neglected drama raises. An important and often misconstructed and misinterpreted passage of Oedipus the King is also dealt with.